INFORMATION SUPPORT OF CONTROLLING OF COMPLEX PRODUCTS IN THE KNOWLEDGE-INTENSIVE INDUSTRIES - M. Cherkasov; A. Zinchenko; M. Bobrova (Вестник университета, 2016)
Market research of the information systems applied in case of management of designing and production at the entities of the knowledge-intensive industries is carried out. the main functions are revealed and characteristics of the integrated information system of controlling of complex products which application will allow to reduce costs for creation of products are determined. the structure and standard structure of the integrated information system is offered.